Clausewitz in the twenty-first century - Strachan, Hew.; Herberg-Rothe, Andreas (Oxford : Oxford University Press, 2007)
This volume considers Clausewitz's timeless'On War' against the background of actual armed conflict. With scholars from a range of disciplines and countries, it throws new light on a classic text and contemporary issues.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Clausewitz, Carl von, -- 1780-1831.; Military art and science; War